Analisis Kualitas Produk dan Harga Terhadap Keputusan Pembelian pada Thrifting Pasar Cimol Gedebage - Utarsih, Henny (Journal of Innovation in Management, Accounting and Business, 2024)
This study aims to determine how much the analysis of product quality and price on purchasing decisions at Thrifting Pasar Cimol Gedebage. The method used in this research is descriptive and verification with primary data in the form of consumer responses regarding product quality and price on purchasing decisions. The sampling technique used was purposive sampling. The statistical analysis used in this study was classical assumption test, validity test, reliability test, multiple linear regression analysis. The number of pupulations and samples in this study were 100 respondents. Sampling using purposive sampling method with sources obtained through the results of filling out questionnaires and processed with the help of SmartPLS software. The results showed that simultaneously and partially Product Quality and Price affect the Thrifting Purchasing Decision of Cimol Gedebage Market.